Post-Purchase Customer Experience Management in Software as a Service Business : Managerial Perspective on B2B Customer Experience from the Service Vendor’s Perspective - Kuokkanen, Juho (My University, 2025)
Software-a-as-Service (SaaS) solutions have been widely adopted over the course of past few decades into business-to-business (B2B) sector where competition of customers intense. Simultaneously the role of the customer experience has become increasingly important competitive factor for companies. However academic research of customer experience in the B2B market has been lacking even though its importance to business success has been proven. The background of this study is the need to understand how Finnish companies providing software services operating in the B2B market manage customer experience in the post purchase stage of the customer journey. The goal of this thesis was to narrow the gap in the contemporary scientific literature on customer experience of B2B markets in the context of software service businesses. To narrow the research gap study used sub questions; how does SaaS as a business model affect customer experience management in the B2B context, how does customer experience management take in to account the different customer organizations and levels within the customer organization, how is the customer experience evaluated. The study was conducted with qualitative approach and as an explorative study where semi-structured expert interviews were used as the data collection method. Thematic analysis was utilized in the study of the collected data, which was used to identify key themes from the interviews. The result show that customer experience and customer experience management were seen as valuable business competitive factors. Both the SaaS business model and operating in the business-to business market had an impact on the customer experience management. The impact of the SaaS business model was emphasized in that the service is the same for all customers, so the customer experience is standardized in a way and the most important factor affecting the customer experience is the software itself. Operating in the B2B market had the effect that customer relationships are both stronger and more distant since only some of the customer organizations representatives have a personal contact with the vendor. The different levels of customer organizations were attempted to be taken into account in different ways, but the most important touch point is the software services user interface. For evaluation of the customer experience a multimethod approach was used. Multimethod approach combines qualitative methods such as feedback gathering and discussions with user and customers representatives and quantitative metrics such as various key performance indicators, usage analytics and customers’ support requests.

Ohjelmistopalvelut (Software-as-a-Service) ovat viime vuosikymmeninä yleistyneet yritysten välisessä liiketoiminnassa (B2B), jossa kilpailu on asiakkaista intensiivistä. Samalla asiakaskokemuksen rooli on korostunut yritysten kilpailutekijänä. Asiakaskokemuksen tutkimus B2B-markkinalla on kuitenkin jäänyt vähemmälle, vaikka sen merkitys yritysten menestymiseen on todistettu. Tämän tutkimuksen taustalla on tarve ymmärtää miten suomalaiset B2B-markkinalla toimivat ohjelmistopalveluyritykset johtavat asiakaskokemusta asiakaspolun jälkiostovaiheessa. Tämän tutkimuksen tavoite oli kaventaa aukkoa nykyisessä tieteellisessä kirjallisuudessa asiakaskokemuksen johtamissa B2B-markinalla ohjelmistopalveluliiketoiminnan kontekstissa. Kaventaakseen tutkimusaukkoa tutkimuksessa käytettiin apukysymyksiä, miten ohjelmistopalveluliiketoimintamalli vaikuttaa asiakas kokemuksen johtamiseen B2B kontekstissa, miten asiakaskokemuksen johtaminen ottaa huomioon erilaiset asiakasorganisaatiot ja tasot asiakasorganisaatioissa ja miten asiakaskokemusta arvioidaan. Tutkimus on laadullinen ja toteutettu eksploratiivisena tutkimuksena, jossa tiedon keruu menetelmänä käytettiin puolistrukturoituja asiantuntijahaastatteluja. Kerätyn aineiston tutkimuksessa hyödynnettiin teema-analyysiä, jonka avulla tunnistettiin keskeiset teemat haastatteluista. Tulokset osoittavat, että asiakaskokemuksen johtaminen ja asiakaskokemus nähtiin arvokkaina liiketoiminnallisina kilpailutekijöinä. Sekä ohjelmistopalveluliiketoiminnalla että yritystenvälisellä markkinalla toimimissa nähtiin vaikutuksia asiakaskokemuksen johtamiseen. Ohjelmistopalveluliiketoiminnan vaikutus korostui siinä, että palvelu on samanlainen tai hyvin vähän kustomoitava kaikille asiakkaille, joten asiakaskokemus on tietyllä tavalla standardoitu ja tärkein asiakaskokemukseen vaikuttava asia on itse ohjelmistopalvelu. Yritysten välisellä markkinalla toimiminen, taas vaikutti siten, että asiakassuhteet ovat samaan aikaan vahvempia, että etäisempiä, koska vain osalla asiakasyrityksen edustajista on henkilökohtainen kontakti toimittajaan. Asiakasorganisaatioiden eritasoja pyrittiin ottamaan huomioon eritavoin, mutta tärkein yksittäinen kosketuspiste on ohjelmistopalvelun käyttöliittymä. Asiakaskokemuksen arviointiin hyödynnettiin monimetodilähestymistapaa, joka yhdistää sekä laadullisia menetelmiä kuten palautteen keruu ja keskustelu, että määrällisiä menetelmiä kuten erilaiset tunnusluvut, käyttöanalytiikan ja asiakkaiden lähettämät tukipyynnöt.
Keywords: B2B, business-to-business, customer experience, customer experience management, Software as a Service, SaaS